Pengaruh Pupuk Bersubsidi Terhadap Pendapatan Petani Padi Sawah Melalui Produktivitas Sebagai Variabel Intervening di Desa Lalos Kecamatan Galang Kabupaten Tolitoli - Hedrat M Nure; Dini Alsa Salsabila (LPPM Universitas Madako Tolitoli, 2026)
This study examines the effect of subsidized fertilizer on the income of lowland rice farmers, with productivity as an intervening variable, in Lalos Village, Galang District, Tolitoli Regency. The research is motivated by delays in the distribution of subsidized fertilizer that force farmers to use non-subsidized fertilizer at higher prices, which affects productivity and farm income. The objective of this study is to analyze the direct effect of subsidized fertilizer on farmers’ income and rice productivity, the effect of productivity on income, and the mediating role of productivity in the relationship between subsidized fertilizer and farmers’ income. The study applies a quantitative approach with a survey design. The population consists of 276 rice farmers, with a sample of 73 respondents selected using simple random sampling. Data were collected through questionnaires and analyzed using multiple linear regression, path analysis, the Sobel test, and the F-test with the assistance of SPSS version 27. The results indicate that subsidized fertilizer has a positive and significant effect on farmers’ income and rice productivity. Rice productivity also has a positive and significant effect on farmers’ income. The Sobel test confirms that productivity acts as a partial mediating variable that strengthens the effect of subsidized fertilizer on farmers’ income. Simultaneously, subsidized fertilizer and productivity have a significant effect on the income of lowland rice farmers. This study highlights the importance of timely and effective distribution of subsidized fertilizer to improve productivity and increase farmers’ income.